Preparation method and application of double-polymer high-voltage electrolyte
By using a bipolymer high-voltage electrolyte formed by mixing polyethylene glycol, polyethylene glycol dimethyl ether and water, the stability and safety of aqueous electrolytes at high voltage are solved, and the high electrochemical stability window and cycle are achieved The life-saving improvement is suitable for supercapacitors, with environmentally friendly and cost-effective advantages.
Patent Information
- Application Number
- CN202411430023.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-14
- Publication Date
- 2025-01-14
- Estimated Expiration
- 2044-10-14
AI Technical Summary
The existing water electrolytes have problems such as toxicity, poor safety, unenvironmental protection, poor high-voltage stability and poor low-temperature resistance, making it difficult to effectively compete with lithium-ion batteries at high voltages.
Polyethylene glycol, polyethylene glycol dimethyl ether and water are mixed to form a bipolymer molecular congested solvent, and lithium bistrifluoromethanesulfonimide is added to form a bisphenyl with high electrochemical stability window and high ionic conductivity. Polymer high voltage electrolyte used in activated carbon//activated carbon symmetric supercapacitors.
It significantly improves the electrochemical stability window and cycle life of the electrolyte, reduces cost and safety risks, broadens the scope of application, and provides environmentally friendly high-voltage electrolyte solutions.
Smart Images

Figure CN119314810A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to a preparation method and application of an aqueous electrolyte. Background Art
[0002] With the growing global energy demand and increasingly severe environmental problems, it is particularly important to develop new, efficient and environmentally friendly energy storage technologies. Compared with mainstream electrochemical energy storage technologies (lithium-ion batteries), aqueous energy storage devices (such as nickel-zinc batteries, nickel-hydrogen batteries, etc.) have the advantages of low cost, environmental friendliness, high power density, and good safety. They are expected to replace lithium-ion batteries in the low- and medium-sized electric vehicle markets, distributed energy storage and other application scenarios. However, due to the poor thermodynamic stability of water, the electrochemical stability window of aqueous electrolytes cannot reach above 1.8V, and cannot match high-voltage and high-capacity electrode materials, resulting in the specific energy density of aqueous energy storage technology being difficult to effectively compete with lithium-ion batteries. At present, the main ways to improve the electrochemical stability window of electrolytes are high-concentration salt (salt-in-water), the use of organic solvents, the introduction of organic additives, etc. Although the above methods can improve the electrochemical stability window of electrolytes to a certain extent, they will also bring about several times the cost increase and toxicity, safety and environmental protection problems. Against this background, the present invention successfully developed a double polymer molecular crowded aqueous high-voltage electrolyte, and provided a preparation method for the above electrolyte, and verified its high-voltage stability using supercapacitors as model devices. Summary of the invention
[0003] The purpose of the present invention is to solve the problems of toxicity, poor safety, environmental pollution, poor high-voltage stability and low-temperature resistance of existing aqueous electrolytes, and to provide a preparation method and application of a dual-polymer high-voltage electrolyte.
[0004] A method for preparing a dual polymer high voltage electrolyte is specifically completed by the following steps:
[0005] 1. Mixing polyethylene glycol, polyethylene glycol dimethyl ether and water, stirring evenly, to obtain an aqueous dual polymer molecular crowded solvent;
[0006] 2. Adding lithium bis(trifluoromethanesulfonyl)imide into an aqueous dual polymer molecular crowded solvent and stirring for a period of time to obtain a dual polymer high voltage electrolyte.
[0007] A dual polymer high voltage electrolyte for application in activated carbon / / activated carbon symmetric supercapacitors.
[0008] Principle of the present invention:
[0009] 1. The present invention innovatively constructs a polyethylene glycol (PEG) / polyethylene glycol dimethyl ether (PEGDME) / H2O aqueous dual polymer molecular crowded solvent, and then uses lithium bis(trifluoromethanesulfonyl)imide (LiTFSI) as a lithium salt, wherein PEG and PEGDME, as macromolecular polymers, contain a large number of functional groups such as ethoxy, amino, and ether groups, which can form hydrogen bonds with water and bind water molecules, thereby reducing the amount of free water, reducing the activity of water, and reducing the tendency of electrolysis (such as hydrogen and oxygen evolution) at high voltage, thereby expanding the electrochemical stability window of the electrolyte; on this basis, an electrolyte salt LiTFSI, which also has high electrochemical stability and is environmentally friendly, is added, so that the aqueous electrolyte prepared in this way not only has a high electrochemical stability window (3.64V) and high ionic conductivity, but also has extremely low cost, safety and environmental friendliness, greatly improving the performance of the aqueous electrolyte at high voltage, broadening the application range of the aqueous electrolyte, and providing a powerful reference for the design of aqueous high-voltage electrolytes.
[0010] Advantages of the present invention:
[0011] 1. The dual polymer high-voltage electrolyte prepared by the present invention is used in activated carbon / / activated carbon (AC / / AC) symmetrical supercapacitors. The test results show that it can work stably in a voltage window as high as 3V and at 2Ag -1 At a current density of 1.5 %, the first cycle discharge capacity can reach 31.3 Fg -1 After 500 cycles, the remaining capacity is 11.3Fg -1 , while the maximum operating voltage of the SC assembled by 2m LiTFSI in H2O is 2.4V, and the first cycle capacity and the cycle capacity of 500 cycles are only 24Fg -1 and 2.4Fg -1 In addition, the SC assembled with 2m LiTFSI in P60PD30H10 electrolyte can be used in 1~5Ag -1 The discharge capacity of the SC assembled with 2mLiTFSI in H2O is about twice that of that of the SC assembled with 2mLiTFSI in H2O at a current density of about 200 ℃. The above shows that the dual polymer high-voltage electrolyte for supercapacitors provided by the present invention has excellent electrochemical properties.
[0012] 2. The significance of the present invention lies in that, through the innovative use of the double polymer molecular crowding effect, not only the electrochemical stability window of the electrolyte is effectively improved, but also the energy density and cycle life are improved, providing new possibilities for improving the performance of aqueous supercapacitors; it not only solves the problem that aqueous electrolytes are easy to decompose under high voltage, but also avoids the significant increase in costs and toxicity, safety, environmental and other issues brought about by the use of high-concentration salts, organic solvents, etc.; in addition, the environmental friendliness and cost-effectiveness of the electrolyte make it have broad application prospects in fields such as large-scale energy storage and electric vehicles; with the growing global demand for sustainable energy technologies, the double polymer molecular crowded aqueous high-voltage electrolyte of the present invention is expected to become one of the key technologies to promote the development of related industries. BRIEF DESCRIPTION OF THE DRAWINGS
[0013] Figure 1 Raman spectra of two electrolytes, 2m LiTFSI in P60PD30H10 and 2m LiTFSI in H2O, prepared in Example 1 and Comparative Example 1;
[0014] Figure 2 A comparison diagram of the electrochemical stability windows of two electrolytes, 2 m LiTFSI in P60PD30H10 and 2 m LiTFSI in H2O, prepared in LSV test Example 1 and Comparative Example 1;
[0015] Figure 3 This is a comparison diagram of electrochemical impedance tests of two electrolytes, 2m LiTFSI in P60PD30H10 and 2m LiTFSI in H2O, prepared in Example 1 and Comparative Example 1;
[0016] Figure 4 Symmetric supercapacitors assembled with 2m LiTFSI in P60PD30H10 and 2m LiTFSI in H2O prepared in Example 1 and Comparative Example 1, respectively, were prepared at 1Ag. -1 Current density, constant current charge and discharge test comparison chart under different voltage windows;
[0017] Figure 5 Symmetric supercapacitors assembled with 2m LiTFSI in P60PD30H10 and 2m LiTFSI in H2O prepared in Example 1 and Comparative Example 1, respectively, were prepared at 1Ag. -1 ~5Ag -1 Rate performance test diagram under current density, in which a is 2m LiTFSI in H2O and b is 2m LiTFSI in P60PD30H10;
[0018] Figure 6Symmetric supercapacitors assembled with 2m LiTFSI in P60PD30H10 and 2m LiTFSI in H2O prepared in Example 1 and Comparative Example 1, respectively, at a current density of 2A -1 Cyclic stability test diagram under the conditions of;
[0019] Figure 7 Comparison of electrochemical stability windows of electrolytes with different PEG to water ratios for LSV testing;
[0020] Figure 8 This is a comparison chart of the electrochemical stability windows of electrolytes with 30% of different types of second solvents added when the PEG ratio is 60% in the LSV test. DETAILED DESCRIPTION
[0021] Specific implementation method 1: This implementation method is a method for preparing a dual polymer high-voltage electrolyte, which is specifically completed according to the following steps:
[0022] 1. Mixing polyethylene glycol, polyethylene glycol dimethyl ether and water, stirring evenly, to obtain an aqueous dual polymer molecular crowded solvent;
[0023] 2. Adding lithium bis(trifluoromethanesulfonyl)imide into an aqueous dual polymer molecular crowded solvent and stirring for a period of time to obtain a dual polymer high voltage electrolyte.
[0024] Specific implementation method 2: This implementation method is different from the specific implementation method 1 in that the number average molecular weight of the polyethylene glycol described in step 1 is 200. The other steps are the same as those in the specific implementation method 1.
[0025] Specific implementation method 3: This implementation method is different from specific implementation method 1 or 2 in that the mass fraction of polyethylene glycol in the water-based dual polymer molecular crowding solvent described in step 1 is 50% to 70%. The other steps are the same as those of specific implementation method 1 or 2.
[0026] Specific embodiment 4: This embodiment differs from specific embodiments 1 to 3 in that the mass fraction of polyethylene glycol dimethyl ether in the water-based dual polymer molecular crowding solvent described in step 1 is 20% to 40%. The other steps are the same as those of specific embodiments 1 to 3.
[0027] Specific embodiment 5: This embodiment differs from specific embodiments 1 to 4 in that the mass fraction of water in the water-based dual polymer molecular crowding solvent described in step 1 is 5% to 15%. The other steps are the same as those of specific embodiments 1 to 4.
[0028] Specific embodiment 6: This embodiment differs from specific embodiments 1 to 5 in that the concentration of lithium bis(trifluoromethanesulfonyl)imide in the dual polymer high-voltage electrolyte described in step 2 is 1.5 mol / kg to 2.5 mol / kg. The other steps are the same as those of specific embodiments 1 to 5.
[0029] Specific embodiment 7: This embodiment differs from specific embodiments 1 to 6 in that the stirring speed in step 2 is 100 r / min to 1000 r / min, and the stirring time is 1 h to 2 h. The other steps are the same as those of specific embodiments 1 to 6.
[0030] Specific embodiment eight: This embodiment is an application of a dual polymer high-voltage electrolyte in an activated carbon / / activated carbon symmetrical supercapacitor.
[0031] Specific embodiment 9: This embodiment differs from specific embodiments 1 to 8 in that: the preparation method of the activated carbon / / activated carbon symmetrical supercapacitor is specifically completed according to the following steps:
[0032] 1. Preparation of activated carbon electrode:
[0033] The activated carbon, conductive carbon black and polyvinylidene fluoride are mixed uniformly and ground to obtain a mixed electrode powder; N-methylpyrrolidone is added to the mixed electrode powder at a stirring speed of 150 r / min to 200 r / min, mixed uniformly, and stirred for a period of time to obtain an AC electrode slurry; the AC electrode slurry is uniformly coated on an aluminum foil and then dried to obtain an activated carbon electrode;
[0034] 2. Assembling activated carbon / / activated carbon symmetrical supercapacitor:
[0035] The positive battery case, the positive electrode sheet, the glass fiber diaphragm, the negative electrode sheet, the gasket, the shrapnel, and the negative battery case are stacked in this order, and a dual polymer high-voltage electrolyte is dripped on one side of the glass fiber diaphragm. After being sealed by a button battery sealing machine, a supercapacitor is obtained;
[0036] The positive electrode sheet described in step 2 is the activated carbon electrode prepared in step 1;
[0037] The negative electrode sheet in step 2 is the activated carbon electrode prepared in step 1. The other steps are the same as those in specific embodiments 1 to 8.
[0038] Specific embodiment 10: This embodiment differs from specific embodiments 1 to 9 in that: the activated carbon described in step 1 is YP-80F; the mass ratio of activated carbon, conductive carbon black and polyvinylidene fluoride described in step 1 is 8:1:1; the grinding time described in step 1 is 1h to 2h; the volume ratio of N-methylpyrrolidone described in step 1 to the mass ratio of activated carbon is 3mL:0.4g; the stirring speed described in step 1 is 200r / min to 800r / min, and the stirring time is 4h to 6h; the drying temperature described in step 1 is 70℃ to 90℃, and the drying time is 10h to 12h. The other steps are the same as specific embodiments 1 to 9.
[0039] The following examples are used to verify the beneficial effects of the present invention:
[0040] Example 1: A method for preparing a dual polymer high voltage electrolyte is specifically completed by the following steps:
[0041] 1. Mix 3 g of polyethylene glycol (PEG), 1.5 g of polyethylene glycol dimethyl ether (PEGDME) and 0.5 g of water, and stir evenly to obtain an aqueous dual polymer molecular crowded solvent;
[0042] The number average molecular weight of the polyethylene glycol described in step 1 is 200;
[0043] The mass fraction of polyethylene glycol in the water-based dual polymer molecular crowding solvent described in step 1 is 60%, the mass fraction of polyethylene glycol dimethyl ether is 30%, and the mass fraction of water is 10%;
[0044] 2. Add 0.01 mol of lithium bis(trifluoromethanesulfonyl)imide into an aqueous dual polymer molecular crowded solvent and stir at 450 r / min for 1 h to obtain a dual polymer high-voltage electrolyte (2 m LiTFSI in P60PD30H10).
[0045] Application Example 1: Assembling activated carbon using 2 m LiTFSI in P60PD30H10 electrolyte prepared in Example 1 / / Activated carbon symmetric supercapacitor (SC) is completed according to the following steps:
[0046] 1. Mix 0.4 g of activated carbon (YP-80), 0.05 g of conductive carbon black (Super P) and 0.05 g of polyvinylidene fluoride (PVDF) evenly, grind for 1 h to obtain a mixed electrode powder; add 3 mL of N-methylpyrrolidone to the mixed electrode powder at a stirring speed of 200 r / min, mix evenly, and then stir at 500 r / min for 5 h to obtain an AC electrode slurry; evenly coat the AC electrode slurry on an aluminum foil, and then dry at 80°C for 12 h to obtain an activated carbon electrode;
[0047] 2. Assembling activated carbon / / activated carbon symmetrical supercapacitor:
[0048] The positive battery case, the positive electrode sheet, the glass fiber separator, the negative electrode sheet, the gasket, the shrapnel, and the negative battery case are stacked in this order, 0.4 mL of the 2 m LiTFSI in P60PD30H10 electrolyte prepared in Example 1 is dropped on one side of the glass fiber separator (with a diameter of 19 mm), and the supercapacitor is obtained after being sealed with a button battery sealing machine;
[0049] The positive electrode sheet described in step 2 is the activated carbon electrode prepared in step 1;
[0050] The negative electrode sheet described in step two is the activated carbon electrode prepared in step one.
[0051] Comparative Example 1: The preparation method of 2m LiTFSI in H2O electrolyte is completed according to the following steps:
[0052] 0.01 mol of lithium bis(trifluoromethanesulfonyl)imide was added to 5 g of water and stirred at 450 r / min for 1 h to obtain 2 mL of LiTFSI in H2O electrolyte.
[0053] Comparative Application Example 1: Assembling activated carbon using 2 m LiTFSI in H2O electrolyte prepared in Comparative Example 1 / / Activated carbon symmetric supercapacitor (SC) is completed according to the following steps:
[0054] 1. Mix 0.4 g of activated carbon (YP-80), 0.05 g of conductive carbon black (Super P) and 0.05 g of polyvinylidene fluoride (PVDF) evenly, grind for 1 h to obtain a mixed electrode powder; add 3 mL of N-methylpyrrolidone to the mixed electrode powder at a stirring speed of 200 r / min, mix evenly, and then stir at 500 r / min for 5 h to obtain an AC electrode slurry; evenly coat the AC electrode slurry on an aluminum foil, and then dry at 80°C for 12 h to obtain an activated carbon electrode;
[0055] 2. Assembling activated carbon / / activated carbon symmetrical supercapacitor:
[0056] The positive battery case, the positive electrode sheet, the glass fiber separator, the negative electrode sheet, the gasket, the shrapnel, and the negative battery case were stacked in this order, and 0.4 mL of the 2 m LiTFSI in H2O electrolyte prepared in Comparative Example 1 was dropped on one side of the glass fiber separator (with a diameter of 19 mm), and the supercapacitor was obtained after being sealed by a button battery sealing machine;
[0057] The positive electrode sheet described in step 2 is the activated carbon electrode prepared in step 1;
[0058] The negative electrode sheet described in step two is the activated carbon electrode prepared in step one.
[0059] Figure 1 Raman spectra of two electrolytes, 2m LiTFSI in P60PD30H10 and 2m LiTFSI in H2O, prepared in Example 1 and Comparative Example 1;
[0060] like Figure 1 As shown in the figure, the OH stretching vibration in 2m LiTFSI in H2O shows a relatively obvious broad peak, with about 3200cm -1 、3400cm -1 、3580cm -1 The positions correspond to the strong hydrogen, weak hydrogen, and non-hydrogen bond peaks, respectively. PEG and PEGDME polymers were added to the 2m LiTFSI inP60PD30H10 solvent. The large number of ether oxygen atoms contained in the repeating structure of the polymer main chain have high electronegativity and can act as hydrogen bond acceptors to interact with hydrogen bond donors in water molecules to form hydrogen bonds and bind water molecules. At the same time, PEG contains hydroxyl groups (-OH) at the end. These terminal hydroxyl groups can act as hydrogen bond donors to form hydrogen bonds with oxygen atoms in water, further binding water molecules and reducing the free water content. The activity of water is further reduced, which corresponds to the decrease in the intensity of strong hydrogen bonds and weak hydrogen bonds in the Raman map, while the intensity of non-hydrogen bonds increases, and the peaks at about 3830cm -1 The peak at the OH bond vibration corresponds to the water molecules not bound by hydrogen bonds, indicating that in the electrolyte after PEG and PEGDME were added to the solvent, most of the water molecules existed in isolation or did not form hydrogen bonds with the surrounding water molecules.
[0061] The linear sweep voltammetry (LSV) curves of 2 m LiTFSI in P60PD30H10 and 2 m LiTFSI in H2O electrolyte were measured by three electrodes on a CHI660E electrochemical workstation using Ag / AgCl reference electrode and titanium foil as working electrode and counter electrode in a Swagelok cell at a scan rate of 0.2 mV s -1 The voltage range is -2 to 3 (Vvs.Ag / AgCl), and the electrochemical stability window of the two electrolytes is determined by using ±20μA as the cutoff current. Figure 2 As shown;
[0062] Figure 2 A comparison diagram of the electrochemical stability windows of two electrolytes, 2 m LiTFSI in P60PD30H10 and 2 m LiTFSI in H2O, prepared in LSV test Example 1 and Comparative Example 1;
[0063] from Figure 2It can be seen that the electrochemical stability window of 2m LiTFSI in P60PD30H10 electrolyte is 3.64 V, while the electrochemical stability window of 2mLiTFSI in H2O electrolyte is only 2.0 V. This shows that the use of dual polymer molecular crowding agents can greatly improve the electrochemical stability window of aqueous electrolytes.
[0064] In order to compare the ion transport performance of 2 m LiTFSI in P60PD30H10 and 2 m LiTFSI in H2O electrolytes, a stainless steel / / stainless steel blocking cell was assembled and the electrochemical impedance spectroscopy (EIS) of the two electrolytes was tested. Figure 3 As shown;
[0065] Figure 3 This is a comparison diagram of electrochemical impedance tests of two electrolytes, 2m LiTFSI in P60PD30H10 and 2m LiTFSI in H2O, prepared in Example 1 and Comparative Example 1;
[0066] from Figure 3 It can be seen that the electrochemical impedance of 2m LiTFSI in P60PD30H10 electrolyte is the smallest and the ionic conductivity is the highest.
[0067] The actual working voltage window of the supercapacitor device is not only related to the performance of the electrolyte, but may also be affected by multiple factors such as the type of electrode material, so the actual working voltage window may not be exactly the same as the electrochemical stability window of the electrolyte. In order to further test the electrochemical performance and application potential of the 2m LiTFSI in P60PD30H10 electrolyte in the present invention, the constant current charge and discharge curve (GCD) of the assembled AC / / AC symmetrical supercapacitor was tested to observe the actual working voltage window of the symmetrical capacitor. Figure 4 As shown in a, the symmetrical supercapacitor assembled with 2m LiTFSI in P60PD30H10 can operate at around 3V without electrolyte decomposition; at the same time, Figure 4 As shown in Figure b, the GCD curve of the symmetrical supercapacitor assembled with 2m LiTFSI in H2O is significantly deformed when charged to about 2.2V, indicating that the electrolyte has decomposed. When charged to 2.7V, the curve is severely deformed and the capacity reversibility is also severely reduced. Therefore, the actual operating voltage window of the device with this electrolyte is only about 2.2V.
[0068] Symmetric supercapacitors assembled from 2 m LiTFSI in H2O at 1 Ag -1 ~5Ag -1 The rate performance test is carried out at the current density such as Figure 5As shown in a, the symmetric supercapacitors assembled with 2 m LiTFSI in P60PD30H10 and 2 m LiTFSI in H2O electrolytes have a high conductivity at 1 Ag. -1 ~5Ag -1 The rate performance test is carried out at the current density such as Figure 5 As shown in b. By calculation, the discharge capacity of the symmetrical supercapacitor assembled with 2m LiTFSI in P60PD30H10 at the same current density is about twice that of the symmetrical supercapacitor assembled with 2m LiTFSI in H2O.
[0069] AC / / AC symmetric supercapacitors assembled from 2 m LiTFSI in P60PD30H10 and 2 m LiTFSI in H2O at a current density of 2A -1 Under the condition of , the capacity retention rate after 500 cycles is as follows Figure 6 As shown, it can be seen that after 500 repeated charge and discharge cycles, the capacitor assembled with 2m LiTFSI in P60PD30H10 can still maintain 36% of the initial capacitance value, while the capacitor assembled with 2mLiTFSI in H2O only maintains 10% of the initial capacitance value, indicating that 2m LiTFSI in P60PD30H10 electrolyte has relatively excellent cycle performance.
[0070] In order to determine the effect of solvents with different PEG contents on the performance of the electrolyte, 2m LiTFSI solutions with different proportions of PEG and water mixed solvents were prepared as electrolytes, with the mass fraction of PEG in the solvent ranging from 30% to 60% and the mass fraction of water ranging from 70% to 40%. In order to compare the electrochemical stability windows of the above four electrolytes, the linear sweep voltammetry (LSV) curves of the above electrolytes were tested on a CHI660E electrochemical workstation using three electrodes in a Swagelok cell with an Ag / AgCl reference electrode and titanium foil as the working electrode and counter electrode. Figure 7 As shown, when the PEG content is 60%, the electrolyte has the largest electrochemical stability window.
[0071] In addition, a 2m LiTFSI solution with a PEG content of 60% was prepared, and 30% by mass of polyethylene glycol dimethyl ether (PD), acetonitrile (AN), methanol (JC), ethanol (YC), and ethylene glycol (EG) were added as solvents. The electrochemical stability windows of the above five electrolytes were tested using the same method, such as Figure 8 As shown, the electrolyte using PEG60PD30H10 solvent has the widest electrochemical stability window, while the electrolytes using other solvents all have side reactions to varying degrees, resulting in a lower electrochemical stability window.
Claims
1. A method for preparing a dual polymer high voltage electrolyte, characterized in that The preparation method is specifically completed according to the following steps:
1. Mixing polyethylene glycol, polyethylene glycol dimethyl ether and water, stirring evenly, to obtain an aqueous dual polymer molecular crowded solvent; 2. Adding lithium bis(trifluoromethanesulfonyl)imide into an aqueous dual polymer molecular crowded solvent and stirring for a period of time to obtain a dual polymer high voltage electrolyte.
2. The method for preparing a dual polymer high voltage electrolyte according to claim 1, characterized in that The number average molecular weight of the polyethylene glycol described in step 1 is 200.
3. The method for preparing a dual polymer high voltage electrolyte according to claim 1, characterized in that The mass fraction of polyethylene glycol in the water-based dual polymer molecular crowding solvent described in step 1 is 50% to 70%.
4. The method for preparing a dual polymer high voltage electrolyte according to claim 1, characterized in that The mass fraction of polyethylene glycol dimethyl ether in the water-based double polymer molecular crowding solvent described in step 1 is 20% to 40%.
5. The method for preparing a dual polymer high voltage electrolyte according to claim 1, characterized in that The mass fraction of water in the water-based dual polymer molecular crowding solvent described in step 1 is 5% to 15%.
6. The method for preparing a dual polymer high voltage electrolyte according to claim 1, characterized in that The concentration of lithium bis(trifluoromethanesulfonyl)imide in the dual polymer high-voltage electrolyte in step 2 is 1.5 mol / kg to 2.5 mol / kg.
7. The method for preparing a dual polymer high voltage electrolyte according to claim 1, characterized in that The stirring speed in step 2 is 100 r / min to 1000 r / min, and the stirring time is 1 h to 2 h.
8. Application of a dual polymer high voltage electrolyte prepared by the preparation method according to claim 1, characterized in that A dual polymer high voltage electrolyte for application in activated carbon / / activated carbon symmetric supercapacitors.
9. The use of a dual polymer high voltage electrolyte according to claim 8, characterized in that The preparation method of the activated carbon / / activated carbon symmetrical supercapacitor is specifically completed according to the following steps:
1. Preparation of activated carbon electrode: The activated carbon, conductive carbon black and polyvinylidene fluoride are mixed uniformly and ground to obtain a mixed electrode powder; N-methylpyrrolidone is added to the mixed electrode powder at a stirring speed of 150 r / min to 200 r / min, mixed uniformly, and stirred for a period of time to obtain an AC electrode slurry; the AC electrode slurry is uniformly coated on an aluminum foil and then dried to obtain an activated carbon electrode; 2. Assembling activated carbon / / activated carbon symmetrical supercapacitor: The positive battery case, the positive electrode sheet, the glass fiber diaphragm, the negative electrode sheet, the gasket, the shrapnel, and the negative battery case are stacked in this order, and a dual polymer high-voltage electrolyte is dripped on one side of the glass fiber diaphragm. After being sealed by a button battery sealing machine, a supercapacitor is obtained; The positive electrode sheet described in step 2 is the activated carbon electrode prepared in step 1; The negative electrode sheet described in step two is the activated carbon electrode prepared in step one.
10. The use of a dual polymer high voltage electrolyte according to claim 9, characterized in that The activated carbon described in step one is YP-80F; the mass ratio of the activated carbon, conductive carbon black and polyvinylidene fluoride described in step one is 8:1:1; the grinding time described in step one is 1h~2h; the mass ratio of the volume of N-methylpyrrolidone described in step one to the activated carbon is 3mL:0.4g; the stirring speed described in step one is 200r / min~800r / min, and the stirring time is 4h~6h; the drying temperature described in step one is 70℃~90℃, and the drying time is 10h~12h.
Citation Information
Patent Citations
Bionic aqueous electrolyte, preparation method and application in supercapacitor
CN112053857A
Electrolyte for high-voltage supercapacitor and high-voltage supercapacitor
CN114121499A
Aqueous double-electric-layer supercapacitor electrolyte and preparation method and application thereof
CN117766304A
Deck road that is easy to adjust the longitudinal inclination and prevents deformation and construction method of the deck road
KR102706768B1
Composition for polymer electrolyte, polymer electrolyte comprising the same, and method for manufacturing polymer electrolyte
US20220093968A1